Seyyed Hossein Nasr’s Perennialism Perspective for the Development of Religious Studies in Indonesia - Syarif Hidayatullah; Mahmud Arif; Arqom Kuswanjono (Jurnal Filsafat "WISDOM", 2023)
One of phenomena that can be analyzed in modern life of human being nowadays is the dysfunction of religion in the social sphere and the development of science and technology. In the context of getting a solution on such modernity crisis, Seyyed Hossein Nasr offers perennial philosophy, by representing Islamic traditional wisdom in modern life of human beings who suffer from a loss of spiritual dimension. This research aims, first, to know the perspective of Seyyed Hossein Nasr's perennial philosophy, and, second, to explore the relevance of perennial philosophy in Seyyed Hossein Nasr's thought about the study of religion. The research results are: firstly, perennial philosophy is a monumental work of Seyyed Hossein Nasr that unites among religion of Islam, philosophy, and science. For Nasr, perennial philosophy is a universal knowledge; that applies eternal and lasting values or norms which emerged from religion throughout the history of human being. Secondly, Nasr offers perennial philosophy as a perspective for study on religions, especially Islam. According to Nasr, there are three responses, namely: firstly, to criticize modern human being whose non-spirituality caused by secularist paradigm of the West modern science and technology; secondly, excavation and reinforcement of the traditional wisdom; and, thirdly, unity or meeting point of all religions in eternal universal principles.